Twice-Exceptionality in High School: a case study of neuropsychopedagogical mediation in strengthening executive functions: Dupla-excepcionalidade no Ensino Médio: um estudo de caso com mediação neuropsicopedagógica no fortalecimento das funções executivas (Papeles, 2026)
Introduction: The inclusion of students with atypical learning profiles still poses a challenge to traditional pedagogical practices , especially when Giftedness/High Abilities (GHA) coexists with neurodevelopmental disorders, such as Attention Deficit Hyperactivity Disorder (ADHD). Methodology: This article analyzes a qualitative case study conducted during supervised internship in Neuropsychopedagogy , focusing on the monitoring of a 3rd-year high school student diagnosed with ADHD and GHA in Mathematics. The objective was to understand the cognitive, emotional, and social manifestations associated with twice-exceptionality and to propose pedagogical strategies that would favor the student's integral development. The study was conducted in a public school in Sobral–CE and involved direct observation, field journal records, and the application of structured interventions. The actions included activities focused on academic organization, verbalization of logical reasoning, and mediated socialization. Results and discussion: The results indicated significant advances in the student's executive functions, self-confidence, and social interactions, demonstrating that neuropsychopedagogical mediation, when based on sensitive listening and the dialogue between cognition and emotion, can enhance both academic performance and symbolic inclusion. Conclusion: It is concluded that personalized pedagogical practices, combined with an interdisciplinary understanding of the individual, are determining factors for successful learning and the effective inclusion of twice-exceptional students.
Keywords: Altas habilidades/superdotação; dupla-excepcionalidade; inclusão escolar; neuropsicopedagogia; Transtorno de Déficit de Atenção com Hiperatividade